Ethnopopulist denial and crime relativisation in Bosnian Republika Srpska - Barton Hronešová, J (Taylor & Francis, 2021)
Ethnopopulist denial has become an essential part of the political repertoire of the political leadership of Republika Srpska (RS) in Bosnia and Herzegovina. It has turned into an effective strategy to preserve power, appeal to voters and disparage internal opposition and international institutions. This article traces the origins of denial and relativisation of the past, outlining the main mechanisms, discourses and processes of leveraging denial as part of the ethnopopulist repertoire. It also depicts how and why denial resonates with the public and why. The article argues that the RS leadership escalates denial when its power is challenged.